PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS PEMECAHAN MASALAH BERBANTUAN ADOBE CAPTIVATE MATERI MATRIKS DI SEKOLAH MENENGAH KEJURUAN (SMK) 3 KOTABUMI - Rahmawati, Nisa Umi; Nugroho, Purna Bayu; Dinata, Karsoni Berta; Truong, Anh Thi Thuy (International Journal of Progressive Mathematics Education, 2023)
Background. Technological advances and developments in the modern era like today are creating new mindsets and patterns of behavior in society. This also affects development in the field of education. Many studies have been carried out but only focus on utilization. Research Methods This research is a Research and Development (R&D) study which aims to develop problem-solving based learning videos. Data analysis in this study used descriptive analysis where the validation results were the quality of the development results. Research Results The results of the final assessment by material experts were 77.5% and with the criteria of "decent, no need for revision". The results of the media expert's assessment are 90% and have received the title "very decent, no need for revision". Assessment by linguists received the title "proper, no need for revision" by obtaining a score of 73.3%. The last assessment was carried out by educational practitioners, the results of the assessment given were 84% and received the title "very decent, no need for revision". The contribution of this research adds to the research contribution in the field of learning video development.   Latar belakang. Kemajuan dan perkembangan teknologi pada era modern seperti saat ini menciptakan pola pikir dan pola perilaku yang baru di masyarakat. Hal tersebut juga mempengaruhi pengembangan dalam bidang pendidikan. Banyak penelitian sudah dilakukan namun hanya berfokus pada pemanfaatan. Metode Penelitian Penelitian ini merupakan Penelitian Research and Development (R&D) yang bertujuan untuk mengembangkan video pembelajaran berbasis pemecahan masalah. Analisis data penelitian ini menggunakan analisis deskriptif dimana hasil validasi merupakan kualitas dari hasil pengembangan. Hasil Peneltian Hasil penilaian akhir oleh ali materi 77,5% dan dengan kriteria “layak, tidak perlu revisi”. Hasil penilaian ahli media 90% dan sudah mendapat predikat “sangat layak, tidak perlu revisi”.  Penilaian oleh ahli bahasa mendapatkan predikat “layak, tidak perlu revisi’’ dengan memperoleh nilai 73.3%. Penilaian terakhir dilakukan oleh praktisi pendidikan, hasil penilaian yang diberikan yaitu84%dan mendapat predikat “sangat layak, tidak perlu revisi”. Kontribusi Penelitian ini menambah kontribusi penetian dibidang pengembangan video pembelajaran.